Avaliação psicométrica da escala de alfabetização financeira em estudantes universitários - Peñaloza Arana, Eloyna Lucia (2024)
Objective: To evaluate the Financial Culture Scale as a psychometrically robust tool for measuring the key dimensions of financial culture in university students in Peru. Methods: A quantitative study was conducted, including the analysis of items through polychoric correlations and the examination of the internal structure and reliability of the instrument. Results: The validity (X²/gl = 3.65; CFI = 0.99; TLI = 0.99; SRMR = 0.03; RMSEA = 0.05; PNFI = 0.91) and reliability of the ESCF were demonstrated, with values exceeding 0.70 and an average variance extracted (AVE) greater than 0.50 in all all dimensions. Conclusion: The validity and reliability of the ESCF have been demonstrated, supporting its use as an effective tool in research. The findings indicate that the model fits the data, suggesting that the evaluated dimensions are consistent and relevant. This provides a solid foundation for future research and applications of the ESCF in various contexts, ensuring that the results are reliable and useful for informed decision-making.